Problems of the international tourism market improvement in Georgia (Economics and region, 2019)
The paper analyzes the current state of the international tourism market development and presents current problems hampering its development in Georgia. Based on this analysis, the authors offer practical recommendations to improve the competitiveness of the tourism Georgia market in the world market of international tourism services. This has a direct impact on the economic development of the country.
Keywords: business processes; business model; enterprise; reengineering; logistic concept; classification criteria